The influence of tax burden, foreign ownership and company size on transfer pricing in securities companies listed on the Indonesian Stock Exchange 2019–2022 - Ahdiana, Aviv Nur; Yuniarti, Rita (WIM Solusi Prima, 2024)
This study aims to investigate the impact of tax burden, foreign ownership, and company size on transfer pricing among securities firms listed on the Indonesia Stock Exchange during 2019–2022. The independent variables analyzed include tax burden, foreign ownership, and company size, with transfer pricing as the dependent variable. Logistic regression was employed for hypothesis testing using SPSS (version 26). The quantitative-descriptive data in this study were derived from documentation and analyzed through a logistic regression model. The study population comprises all financial statements of securities firms from 2019–2022. Purposive sampling, based on complete financial report publications from this period and excluding firms with losses, resulted in a sample of 52 samples. Findings reveal a negative association between tax and transfer pricing, a negative relationship between foreign ownership and transfer pricing, while company size showed no effect on transfer pricing.